Technological innovation in the Cooperativa de Caficultores del Cauca CAFICAUCA - Narváez - Ordoñez , Susan Deisy; Barreda - Ramírez, Concepción; Velasco - Hurtado, Dora Silvana; Bejarano - Orozco, Germán; Certuche - Muñoz, Paola Marcela (Universidad Francisco de Paula Santander, 2020)
This article presents the research that determines the level of technological innovation of the Cauca-CAFICAUCA Coffee Growers' Cooperative, a company with 2981 members in the Department. A cross-sectional descriptive study was developed, for which an intentional probabilistic sample of 15 people in coordination and management positions was taken, to which a self-evaluation survey of business innovation management was applied based on (Sánchez, Pozo, Rabadan, & Trujillo, 2009), a diagnostic questionnaire from Monterrey (2013) and indicators for measuring innovation from Lugones (2015). It was concluded that the level of innovation is located in scenario B, or little advanced state in innovation. The culture of innovation is limited and no threats are perceived by the evolution of competition.